Understanding actor roles in sustainability initiatives: An exploratory study in five European countries - Jennifer Hauck; Ines Omann; Ines Thronicker; Wouter Spekkink; Alberto Díaz Ayude; Fridanna Maricchiolo; Mirijam Mock; Jaco Quist; Vlad Pandur (Helmholtz-Zentrum für Umweltforschung (UFZ), 2020)
Several strands of literature have developed around the ambition to influence or bring about transitions toward greater sustainability. In this context researchers have come to be interested in the types of actors involved in sustainability transitions and the roles these actors play. However, there is a lack of clear definitions of actors, and their roles. Our research takes an exploratory approach and is designed to describe and analyse the actors concerned and to identify their roles in sustainability initiatives. Our aim in doing so is to contribute to the body of scientific knowledge on transitions and to provide sustainability initiatives themselves with helpful information. Data were collected using the Net-Map tool, a well-established method in actor and stakeholder analysis. In our results we identify and define six actor roles: catalysts, opponents, intermediaries, frontrunners, drivers and visionaries. In the literature, particular roles are connected to common actor categories (civil society, governmental actors, private sector, etc.). Our results imply that sustainability initiatives are neither necessarily hindered by the absence of certain actors, nor are they hindered per se by the presence of an actor - rather, a broad mix seems to be helpful.
Keywords: 330; transdisciplinarity; stakeholder analysis; social networks; local experiments; intermediaries